Seasonal Solar Thermal Absorption Energy Storage Development - Xavier Daguenet-Frick; Paul Gantenbein; Mathias Rommel; Benjamin Fumey; Robert Weber; Kanishka Goonesekera; Tommy Williamson (CHIMIA)
This article describes a thermochemical seasonal storage with emphasis on the development of a reaction zone for an absorption/desorption unit. The heat and mass exchanges are modelled and the design of a suitable reaction zone is explained. A tube bundle concept is retained for the heat and mass exchangers and the units are manufactured and commissioned. Furthermore, experimental results of both absorption and desorption processes are presented and the exchanged power is compared to the results of the simulations.